Diagnostic peculiarities and difficulties of parapharyngeal space tumours - Senkus, Linas; Gibavičienė, Jolita; Čepulis, Vytautas (Lietuvos chirurgija, 2016)
Introduction Parapharyngeal space tumours, most of them benign, account for some 0.5% of head and neck. Since they are rare, most clinicians will only come across a small number of them during their career. Nevertheless, it is important to highlight a few aspects of their diagnostics: symptoms are various and usually nonspecific, and signs manifest when tumour is rather advanced. Materials and methods This article summarizes diagnostic aspects of retrospective analysis of 6 parapharyngeal space tumour cases, treated in National Cancer Institute between 2004 and 2016. We revise the scientific literature and analyse the diagnostic sequence, placing special emphasis on describing difficulties and peculiarities of diagnosing parapharyngeal space tumours. Results 3 benign and 3 malignant tumours were diagnosed. Patients reported a wide variety of symptoms, most of them being nonspecific. The vast majority of patients underwent preoperative fine needle aspiration biopsy (FNAB), and radiological imaging (computed tomography (CT) and/or magnetic resonance imaging (MRI) was performed for all of them. Conclusions All clinicians who come across these cases should take into consideration that symptoms of parapharyngeal space tumours are usually nonspecific, and signs appear after a period of silence. In diagnostic sequence, fine needle aspiration biopsy is mandatory to avoid histological surprises. Radiological imaging, especially MRI, is useful in predicting the origin, side, size and, to some extent, the type of the tumour.